Soil aggregation, organic carbon and microbial Biomass as affected by tillage, residue management and cropping systems in tropical ferralsols of Western Kenya - Bolo, Peter Omondi; Kihara, Job Maguta; Mucheru-Muna, Monicah; Mugendi, Ezekiel; Kinyua, Michael (Kenya Agricultural and Livestock Research Organization, 2023)
Soil aggregates are important indicators of soil health, nutrient status and ability to resist erosion. This parameter is sensitive to soil disturbances that occasion disintegration of aggregate sizes, loss of organic carbon and physical killing of the soil dwelling macro- and micro-fauna. Numerous agronomic practices are promoted to enhance sustainable food production, but little concern has been taken on the effects of such practices on soil aggregate stability and microbial biomass and soil organic carbon, yet these are vital indicators of soil health, nutrient availability and structure maintenance. A study was conducted in western Kenya to assess the effects of tillage, cropping systems and residue management on soil aggregate stability, microbial biomass carbon and soil organic carbon in 2017 and 2020. At both depths assessed (0-5 and 5-15 cm), tillage, cropping systems and residue retention significantly (P ≤ 0.05) affected soil aggregate stability indices. Mean weight diameter (MWD) was significantly higher (P ≤ 0.05) in; Reduced tillage (RT) than conventional tillage (CT) (P ≤ 0.05), maize-soybean intercrop compared to rotation system (P ≤ 0.05), and in residue retention compared to residue removal treatment (P ≤ 0.05). In 2017, microbial biomass carbon (MBC) was not significantly affected by either tillage, reside retention or cropping systems, but was 23 and 29%, respectively, higher in reduced tillage and maize-soybean intercropping systems respectively. In 2020, MBC positively correlated with total nitrogen, SOC and S as opposed to 2017. Soil organic carbon (SOC) was not significantly affected by treatments, but was slightly higher in residue retention (3.57%) and maize-soybean intercropping systems (6.0%). In 2017, large macro-aggregates (LM) at 5 cm depth significantly negatively correlated with Mn while LM (at 15 cm) positively correlated with soil pH, K and Mg. Small macro-aggregates (SM) at 15 cm positively correlated with S but negatively with Al (at both depths), P and Fe. Micro-aggregates (M) at 15 cm positively correlated with P and Al but negatively with Mg. Silt and clay (SC) positively correlated with Al while negatively with Mg and pH at 5 cm. The MWD positively correlated with Ca and Mg. Soil pH and Mg also positively correlated with GMD at 15 cm while Al showed negative correlation. These findings suggest that practicing reduced tillage, combined with residue retention while observing proper cropping systems can markedly reduce the susceptibility of soil to erosion, improve soil organic carbon and increase soil microbial biomass